Development of Nutrition Education Media ‘Sugar-Sweetened Beverages’ Pocket Book for Elementary School - Tsabita, Khansa Mulita; Rahmawaty, Setyaningrum (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to develop nutrition education media in the form of a sugar-sweetened beverages pocketbook for elementary children and examining its validity. Methodology: The type of research used was research & development with 4 sequential steps including analysis, design, development, and evaluation its content va-lidity by 6 experts in the field of nutrition, language, and media. Results: The title of pocket book produced in this study was "sugar-sweetened bever-ages" with a size of 10.5 cm x 14.8 cm (A6) consisting of 39 pages. The font type "Glacial Indifference" with a size of 7 was used, and the booklet was printed on glossy paper with a dominant color scheme of light blue, red, yel-low, and orange. The overall average content validity indexed (CVIs) assessed by the nutrition expert, language, and media were 0.785, 1, and 0.775 which were in very suitable category. Applications/Originality/Value: It can be concluded that this pocket book media on sugar-sweetened beverag-es has met the characteristics of learning media for elementary school chil-dren.